Pengaruh Inflasi, Suku Bunga dan Pertumbuhan PDB Terhadap IHSG - Fathulloh, Moh; Agustina, Rachma (JFAS : Journal of Finance and Accounting Studies, 2023)
This study aims to determine the effect of inflation on the JCI, the effect of interest rates on the JCI, and the effect of GDP growth on the JCI. This research uses SPSS analysis test. In this study, the approach used is a quantitative approach. The sample selection method uses a non-probability sampling method. In this study, the data used are secondary data registered and published in the Central Statistics Agency, Bank Indonesia and the Indonesia Stock Exchange. The sample used in this study was saturated sampling where all the population was sampled as many as 32 data samples during the 2014-2021 period. The results showed that inflation and interest rates had no effect on the Composite Stock Price Index (JCI), while the Gross Domestic Product (GDP) had an effect on the Composite Stock Price Index (JCI).